Insights into microbiota community dynamics and flavor development mechanism during golden pomfret (Trachinotus ovatus) fermentation based on single-molecule real-time sequencing and molecular networking analysis - Yueqi Wang; Qian Chen; Huan Xiang; Dongxiao Sun-Waterhouse; Shengjun Chen; Yongqiang Zhao; Laihao Li; Yanyan Wu (Food Science and Human Wellness)
Popular fermented golden pomfret (Trachinotus ovatus) is prepared via spontaneous fermentation; however, the mechanisms underlying the regulation of its flavor development remain unclear. This study shows the roles of the complex microbiota and the dynamic changes in microbial community and flavor compounds during fish fermentation. Single-molecule real-time sequencing and molecular networking analysis revealed the correlations among different microbial genera and the relationships between microbial taxa and volatile compounds. Mechanisms underlying flavor development were also elucidated via KEGG based functional annotations. Clostridium, Shewanella, and Staphylococcus were the dominant microbial genera. Forty-nine volatile compounds were detected in the fermented fish samples, with thirteen identified as characteristic volatile compounds (ROAV > 1). Volatile profiles resulted from the interactions among the microorganisms and derived enzymes, with the main metabolic pathways being amino acid biosynthesis/metabolism, carbon metabolism, and glycolysis/gluconeogenesis. This study demonstrated the approaches for distinguishing key microbiota associated with volatile compounds and monitoring the industrial production of high-quality fermented fish products.